Cattle breeds: Extinction or quasi-extant? - Bett, R.C.; Okeyo Mwai, Ally; Malmfors, B.; Johansson, K.; Agaba, Morris; Kugonza, Donald R.; Bhuiyan, A.K.F.H.; Filho, A.E.V.; Mariante, A.S.; Mujibi, F.D.N.; Philipsson, J. (MDPI, 2013)
Uniquely selected breeds bred over thousands of years of domestication in awide range of environments have been declared extinct over the last century. Still morebreeds are at risk of becoming extinct and the rate continues to accelerate. Assessing thecurrent status and possible future dynamics of livestock breeds is therefore a critical step inthe management of Animal Genetic Resources (AnGR). This study applies a qualitativeapproach to comprehensively analyze cattle genetic resources in selected countries in orderto better understand the risk status of cattle breeds and those that need to be considered extinct and/or quasi-extant. The status of each breed, i.e., not at risk, critical, endangeredand extinct, was verified using information available at the Domestic Animal DiversityInformation System (DAD-IS) web site, as well as cattle statistics (where available) and abreed survey. In most examples, breeds listed as extinct have played important roles in thedevelopment of new breeds, and should not be classified as extinct, unless provenotherwise, given that even breeds existing in vivo are developing. Therefore, a new riskstatus quasi-extant for this category of cattle breeds is suggested. In addition, based on thefindings of this study, the concept of breed needs to be questioned as relates to it being agood measure of genetic diversity. Further investigations of the situation of cattle breeds (andother livestock species) in more countries/continents using similar categories aredeemed necessary.